UTILIZATION OF AUGMENTED REALITY TECHNOLOGY IN 3D VISUALIZATION OF HIGH SCHOOL OF ADISUTJIPTO TECHNOLOGY BASED ON ANDROID - Kusumaningrum, Anggraini; Ayuningtyas, Astika; Lopes, Jodio Blasius (Jurnal Internasional Teknik, Teknologi dan Ilmu Pengetahuan Alam, 2019)
Adisutjipto College of Technology in introducing campus information that is still using print and internet media, therefore, an application is needed that can introduce and provide information on buildings on campus by utilizing Augmented Reality technology. With the technology of Augmented Reality able to provide real information and can interact directly with buildings on campus. This application was created using the Unity and Vuforia application. Making 3D models using the Google SketchUp application which is then exported to the Unity application. Testing is done to detect markers of light intensity, distance, marker size, and color. From the results of testing markers for light intensity of at least 4 lx and effective detection distance between 20 cm to 40 cm and marker size of at least 350 x 350 Pixels, while the color has no effect due to edge detection which is the basic technique of reading by Vuforia markers. This application has been successfully made in Augmented Reality in the form of STTA 3D visualization as a supporting medium for the introduction of the Adisutjipto College of Technology Yogyakarta environment. This application can only be run on Android-based smartphones with a minimum version of 5.0.